(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Oral health serves as a gateway to general health. Dental diseases have a detrimental effect on the quality of life. A strong relationship exists between various oral and systemic diseases. Thus, prevention and timely treatment of oral diseases like dental caries and periodontal diseases have been shown to reduce the risk of systemic diseases like cardiovascular diseases and diabetes. It reminds the necessity of maintaining an optimal oral hygiene. This can be achieved by regular oral hygiene measures including some Ayurvedic techniques like Dant Dhvani (cleansing or washing the teeth), Jivha Lekhna (tongue scraping) and Kavala Gandoosha (also known as oil pulling) etc. The use of oil pulling can be frequently found in the ancient text on medicine and recent studies have shown tremendous results on the benefits of the technique. This review article provides an insight about the concept of oil pulling or oil swishing, its method of usage, its mechanism of action and its role on preventing various oral diseases. This article also throws light on the link or relationship between dental and Ayurvedic science and the wise usage of Ayurvedic preparations for the maintenance of oral health and the cure of certain oral diseases which had been proven to be effective in the long run.